Validation of a Disability Assessment Tool Based on the International Classification of Functioning, Disability, and Health in the Chinese Context - Li, Jiahui; Qiu, Huaide; Zhang, Xia; Jin, Juan; Zhao, Yuanping; Yan, Juan; Xie, Hong; Liu, Shouguo; Li, Jianan (Frontiers in Rehabilitation Sciences, 2022)
Background: The common standards of disability assessment for long-term care (LTC) insurance are currently absent. The International Classification of Functioning, Disability and Health (ICF) was designed for a better description of health and functioning, which could fill the demand gap for the standards of disability assessment and be a promising tool for the development of LTC insurance system. Objectives: To validate a disability assessment scale for disabled elderly individuals based on the ICF for LTC in the Chinese context. Methods: The present study is a cross-sectional study. A disability assessment tool based on the ICF was developed by referring to other assessment tools and an expert consensus meeting in the initial phase of the study. The developed tool was used to evaluate 1,610 elderly individuals in the LTC institutions. The Cronbach's α coefficient and split-half reliability were applied to test the internal consistency of the tool, while the Interclass correlation coefficients (ICCs) were used to evaluate the interrater reliability (IRR). Factor analysis was performed to verify the construct validity of the tool. The scores from the Medical Outcomes Short Form-12 (SF-12) were correlated with that from the disability assessment tool, to assess the criterion-related validity. Results: The Cronbach's α coefficient and split-half reliability of the disability assessment tool were 0.969 and 0.877, respectively. The ICCs of the sum scale was 0.85, and the ICCs of each of the 20 items in the scale ranged from 0.78 to 0.94. The items were divided into three factors through analysis, which is consistent with the structure expectation. The scores of each item and the sum score of the disability assessment scale were negatively correlated with the scores of the physical and psychological fields in SF-12 (p<0.001). Overall, the data indicated that the tool was characterized by good internal consistency, IRR, construct validity, and criterion-related validity. Conclusions: The disability assessment tool based on the ICF is a reliable and valid tool for the collection of information on functioning across various LTC settings. The information of disability provided evidence for the distribution of LTC service and guided the development of LTC insurance standards.